2023
DOI: 10.1212/wnl.0000000000207942
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sleep Microarchitecture and Cognitive Impairment in Patients With Temporal Lobe Epilepsy

Alex C. Bender,
Afareen Jaleel,
Kyle R. Pellerin
et al.

Abstract: Objectives:To investigate the spatiotemporal characteristics of sleep waveforms in temporal lobe epilepsy (TLE) and examine their association with cognition.Methods:In this retrospective, cross-sectional study, we examined overnight EEG data from adult patients with temporal lobe epilepsy (TLE) and non-epilepsy comparisons (NEC) admitted to the epilepsy monitoring unit (EMU) at Mass General Brigham hospitals. Automated algorithms were used to characterize sleep macro-architecture (sleep stages), and micro-arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In contrast to measures of spike rate, sleep spindle rate predicts IQ, processing speed, and sensorimotor coordination in RE 8 , and changes in spindle rate predict cognitive response to high-dose benzodiazepine treatment in severe epileptic encephalopathies 9 . Similar findings have subsequently been reported in other epilepsy populations 11,12 , suggesting that sleep spindle deficits may provide a robust, generalizable biomarker for several cognitive symptoms observed in epilepsy.…”
Section: Introductionsupporting
confidence: 85%
“…In contrast to measures of spike rate, sleep spindle rate predicts IQ, processing speed, and sensorimotor coordination in RE 8 , and changes in spindle rate predict cognitive response to high-dose benzodiazepine treatment in severe epileptic encephalopathies 9 . Similar findings have subsequently been reported in other epilepsy populations 11,12 , suggesting that sleep spindle deficits may provide a robust, generalizable biomarker for several cognitive symptoms observed in epilepsy.…”
Section: Introductionsupporting
confidence: 85%
“…Bender et al found no significant differences in sleep macroarchitecture, such as sleep efficiency, fragmentation, and time spent in different stages of sleep, between TLE and controls. 6 However, they did observe a notable reduction in sleep microarchitecture, specifically spindle density, in TLE patients, particularly ipsilateral to the side of the ictal onset. 6 This finding suggests a possible link between alteration in sleep microarchitecture and abnormal epileptic network.…”
Section: Commentarymentioning
confidence: 88%
“… 5 Concurrently, Bender et al examined this relationship in adults with temporal lobe epilepsy (TLE), utilizing scalp EEG and/or foramen ovale electrodes. 6 While these studies provided answers to several critical questions, they also opened up many more new avenues of inquiry along the way.…”
Section: Commentarymentioning
confidence: 99%
“…These could be secondary to early involvement of dentate gyrus/CA3 and CA1, subfields responsible for pattern separation and integration ( Figures 3 , 4 ; Table 1 ) ( 29 , 35 ). Furthermore, difficulty with long term consolidation could be secondary to increased frequency of interictal discharges during NREM sleep ( 59 , 60 ) or decreased spindle activity seen during NREM sleep ( 61 ). Additionally, TLE patients with unilateral onset of left or right hemisphere seizures may exhibit a material-specific impairment in memory for verbal or nonverbal material ( 62 ).…”
Section: Characterizing Ad and Loe Cognitive Phenotypesmentioning
confidence: 99%
“…Bilateral frontotemporal slowing and mild slowing and desynchronization in the posterior dominant rhythm have been linked to the degree of amyloid and tau deposition, respectively ( 19 ). Sleep EEG in patients with temporal lobe epilepsy shows decreased spindle density ( 61 ). While mesial temporal IEDs can be difficult to detect with conventional scalp EEG, our center has had improved sensitivity with adding subtemporal (T1/T2) leads.…”
Section: Clinical Diagnosis and Differentiationmentioning
confidence: 99%